Sarcopenia and Pleural Mesothelioma: The Current Knowledge - Nikolaos D. Karakousis; Konstantinos I. Gourgoulianis; Nikolaos Papanas; Ourania S. Kotsiou (Muscles, 2024)
Pleural mesothelioma (PM) is a tumor related to adverse prognosis. The PM WHO classification has mainly identified three major subtypes of PM which are epithelioid, biphasic, and sarcomatoid. Sarcopenia is a medical issue related to a reduction in muscle mass and strength. It represents a major health issue globally because it is related to adverse effects such as hospitalization, increased length of stay, disability, increased morbidity and mortality and augmented health care expenditures. In this literature review, we attempted to examine the upcoming association between sarcopenia and PM. As recorded by the current literature, muscle loss in PM subjects was related to poorer survival and lower levels of activity. Subjects with PM had increased rates of pre-sarcopenia and malnutrition, while pre-sarcopenia was related to worse activity levels, and malnutrition was related to worse quality of life (QoL). Both tumor volume and sarcopenia were related to long-term mortality in surgically treated PM subjects, while sarcopenia was present both pre-operatively and post-operatively in these subjects. In addition, post-operative sarcopenic subjects showed a decreased 3-year overall survival (OS) in comparison with those who did not have sarcopenia, while pre-operative sarcopenia was importantly related to an increased rate of post-operative adverse outcomes. More studies are needed to validate these claims.